Iodine deficiency associated with parenteral nutrition in extreme preterm infants. Issue 1 (1st January 2003) - Ibrahim, M; de Escobar, G Morreale; Visser, T J; Durán, S; van Toor, H; Strachan, J; Williams, F L R; Hume, R
Abstract : Infants are in negative iodine balance on current standard regimens of total parenteral nutrition, with a mean iodine intake of 3 μg/kg/day (150 ml/kg/day). The recommended enteral intake of iodine for preterm infants is 30 μg/kg/day. Gastrointestinal absorption of iodine is high, suggesting that parenteral intakes should approach enteral recommendations.